Ti0.8O2Nanosheets Inhibit Lung Cancer Stem Cells by Inducing Production of Superoxide Anion - Nalinrat Petpiroon; Narumol Bhummaphan; Rapeepun Soonnarong; Wipa Chantarawong; Tosapol Maluangnont; Varisa Pongrakhananon; Pithi Chanvorachote (My University, 2019)
Recent research into the cancer stem cell (CSC) concept has driven progress in the understanding of cancer biology and has revealed promising CSC-specific targets for drug discovery efforts. As malignancies of lung cancer have been shown to be strongly associated with activities of CSCs, we examined the effects of Ti0.8O2 nanosheets on these cells. Here we show that the nanosheets target lung CSCs but not normal primary dermal papilla (DP) stem cells. Whereas Ti0.8O2 caused a dramatic apoptosis along with a decrease in CSC phenotypes, in primary human DP cells such effects of nanosheets have been minimal. Nanosheets reduced the ability of lung cancer cells to generate three-dimensional tumor spheroids, lung CSC markers (CD133 and ALDH1A1), and CSC transcription factors (Nanog and Oct-4). Ti0.8O2 nanosheets reduced CSC signaling through mechanisms involving suppression of protein kinase B (AKT) and Notch-1 pathways. In addition, the nanosheets inhibited the migration and invasive activities of lung cancer cells and reduced epithelial-to-mesenchymal transition (EMT) markers as N-cadherin, vimentin, and Slug, as well as metastasis-related integrins (integrin-αv and integrin-β1). Importantly, we found that the selectivity of the Ti0.8O2 nanosheets in targeting cancer cells was mediated by induction of cellular superoxide anion in cancerous but not normal cells. Inhibition of nanosheet-induced superoxide anion restored the suppression of CSC and EMT in cancer cells. These findings demonstrate a promising distinctive effect of Ti0.8O2 nanosheets on lung CSC that may lead to opportunities to use such a nanomaterial in cancer therapy.
Keywords: MicroRNA in disease regulation